Europa’s ocean: potential for extraterrestrial chemoautotrophy - Barrett, Emory G.; Lutz, Richard A. (Frontiers in Astronomy and Space Sciences, 2025)
The search for extraterrestrial life has historically focused on photosynthetic organisms but following the discovery of deep-sea hydrothermal vents on Earth and the variety of microbes with unconventional metabolic pathways that inhabit them, astrobiology has expanded to encompass the search for extraterrestrial chemoautotrophs. Although bombarded by Jovian radiation and encased in a thick shell of ice, Jupiter’s moon Europa could very well be a sanctuary for extraterrestrial microbial life. It is widely accepted that underneath the ice lies a deep, salty ocean, and, despite possibly anoxic conditions, high pressures, and lack of sunlight, many physical and chemical properties of Europa are analogs of extreme environments on Earth, such as hydrothermal vents or subterranean radiogenic ecosystems. By drawing comparisons between Europa and Earth, it can be seen how processes such as serpentization, water radiolysis, and volcanic activity induced by tidal heating or Jovian radiation could very well be providing energy to chemoautotrophs inhabiting various habitats on the ocean floor. Understanding the possibilities of chemoautotrophic life on Europa can be extended to other planetary bodies, such as Mars and Enceladus, allowing for their consideration under a new perspective. Future missions such as the Europa Clipper, scheduled to arrive in 2030, will provide further clarity on the moon’s habitability and potentially bring science closer to the discovery of extraterrestrial biota.